Gen Z, Lets Talk : Karena Diam Bukan Solusi Pada Mahasiswa Politeknik LP3I - Ernawati Ernawati; Yunan Arifin; Rianty Nugroho Putri (Universitas Perjuangan Tasikmalaya, 2026)
Gen Z is known as a generation born in the digital era characterized by fast, open, and technology-based communication. However, amidst easy access to information and social media, a phenomenon of silence or a tendency towards silent behavior has emerged in social interactions, especially in the campus environment. This activity aims to foster communication awareness among Gen Z to be more open, bold in expressing opinions and not closing themselves off to differences of opinion in academic and social environments, reducing the phenomenon of silent behavior or passive attitudes in communication, both in the classroom, organizations, and digital media, by fostering self- confidence and courage to express opinions. Analyze the communication tendencies of LP3I Polytechnic students as representatives of Gen Z, and understand the factors that influence their courage in expressing opinions and emotions. Quantitative descriptive is a method used through the distribution of questionnaire questions to respondents of active students of LP3I Polytechnic. The main factors causing silence are fear of social judgment, lack of environmental empathy, and a hierarchical communication culture that silence is not a solution in building healthy and productive communication in the Gen Z community. Therefore, it is necessary to strengthen empathetic communication literacy, public speaking training, and support from educational institutions to create a climate of open dialogue that supports the psychological well-being of students.